MARIJUANA USE AND SLEEP ACROSS THE LIFE COURSE: RESULTS FROM THE NATIONAL HEALTH AND NUTRITION EXAMINATION SURVEY. (16th November 2018) - Kaufmann, C; Yourman, L; Moore, A
Abstract: With marijuana legalization in select states, marijuana has emerged as a potentially safer treatment for insomnia. More information is needed on marijuana use and sleep across the life course. We combined data from 2005–2014 National Health and Nutrition Examination Survey to explore differences in self-reported sleep duration and health service use (telling doctor about sleep problem, receiving sleep disorder diagnosis, and sedative-hypnotic medication use) between current, past, and never users of marijuana, and to assess variations across age groups, controlling for year of survey. Overall, 20.7% reported current marijuana use, 39.0% past use, and 40.4% never use. Current use declined with age (35.6% for 18–29 to 11.8% for 50–59 years), while past use increased (25.9% for 18–29 to 47.3% for 50–59). Versus never users, current users had 49% greater odds (95% Confidence Interval [CI]=1.31, 1.69) of telling doctor about sleep problem and 99% greater odds (95% CI=1.46, 2.69) of sedative-hypnotic use, but had no differences in sleep duration and sleep diagnosis. Versus never users, past users self-reported -0.08 (95% CI=-0.14, -0.03) fewer sleep hours, and had 41% greater odds (95% CI=1.19, 1.67) of sleep diagnosis, 64% greater odds (95% CI=1.50, 1.80) of telling doctor about sleep problem, and 97% greater odds (95% CI=1.56, 2.48) of sedative-hypnotic use. Results were similar across age groups. With growing legalization of marijuana, it is likely there will be differences across use patterns for reasons including sleep. As marijuana has promise as a safer substitute for alleviating insomnia than many medications, future study is warranted.